Capacitance of edge-free three-dimensional graphene: New perspectives on the design of carbon structures for supercapacitor applications. (10th October 2022) - Tang, Rui; Nomura, Keita; Inoue, Kazutoshi; Kotani, Motoko; Kyotani, Takashi; Nishihara, Hirotomo
Abstract: The current target for expanding the application scope of supercapacitors is to increase their energy density ( E ) beyond 20 Wh kg −1 . In this regard, edge-free carbon materials show considerable potential because of their high working voltage ( U ) in organic electrolytes; however, their capacitance ( C ) remains limited. In this study, we synthesized edge-free three-dimensional (3D) graphene materials with different numbers of graphene stacking layers ( n stack ). These carbon materials have similar pore morphologies and an edge-free structure because a template method and annealing at 1800 °C were applied, respectively. These features allowed C to remain unaffected by the pore size effect, wettability, parasitic side reactions, and pseudocapacitance. Our results suggested that increasing n stack slightly enhances the areal C ; however, such an increase cannot compensate for the decrease in C attributed to the decrease in the specific surface area. We also confirmed that the C of 3D graphene materials has a quantum origin, which results in a "butterfly shaped" cyclic voltammetry curve; we also successfully quantified the quantum capacitance ( C Q ) for the complete understanding of the origin of C . Based on this knowledge, we estimated that this 3D graphene material can yield a high E of 43 Wh kg −1 once C Q is optimized.